PENGARUH HUBUNGAN INTERPERSONAL DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI DINAS KEBUDAYAAN DAN PARIWISATA SEMARANG - Kusumawati, Ratna (Laporan Penelitian dan Pengabdian Masyarakat, 2024)
INTERPERSONAL RELATIONSHIP AND THE WORK ENVIRONMENT ON EMPLOYEE SATISFACTION Ratna Kusumawati Jurusan Manajemen, Fakultas Ekonomi, Universitas Wahid Hasyim Address: Jl Menoreh Tengah X/22 Sampangan Semarang Abstract This research was conducted at the Semarang tourism and culture office, and aims to determine the interpersonal relationship, work environment and employee job satisfaction and to find out how much influence interpersonal relationships have on employee job satisfaction and how much influence the work environment has on employee job satisfaction. The population in this study were 130 people and the number of samples in this study were 57 people with simple random sampling technique. The method used is a survey method with descriptive analysis techniques and verification. The technique of collecting data is a questionnaire. The data instrument testing was done by using validity and reliability tests, while the data analysis used the Pearson product moment correlation and the coefficient of determination and hypothesis testing with the t test. Based on the results of the research, the Pearson product moment correlation research, the relationship between interpersonal relationships and employee job satisfaction, is in the medium category and is positive. Based on the t test, Ha is accepted and Ho is rejected, meaning that there is a significant influence between interpersonal relationships on employee job satisfaction. Based on the results of the Pearson product moment correlation, the relationship between work environment and employee job satisfaction is categorized as strong and positive. Based on the t test, Ha is accepted and Ho is rejected, meaning that there is a significant influence between the work environment and employee job satisfaction. Keywords: Interpersonal Relationships, Work Environment and Employee Job Satisfaction